ALIH FUNGSI LAHAN PERTANIAN DI KAMPUNG UDAPI HILIR DISTRIK PRAFI KABUPATEN MANOKWARI (SHIFT THE FUNCTION OF AGRICULTURAL LAND IN THE VILLAGE OF UDAPI HILIR PRAFI DISTRICT MANOKWARI DISTRICT ) - Ryvany Dampa; Obadja A. Fenetiruma; Michael A. Baransano (Sosio Agri Papua, 2021)
Land Function Changing is defined as transformation of Land Resourches alocation from previous using to other using. The objctives of this reserach is to know the amount of agricultural land that change to other fuctions, the reasons of land transformation and recent fucntions of land in Udapi Hilir Village, Prafi District, Manokwari Regency. The method that used is description with case study. The result shows that from 100 Ha agricultural land now changed 55,5 Ha to non agricultural fuction. The determination factors are : Income (36), Labour (24%), childrens’ education cost (18%), age (12%), non productive land (6%), and healthcare (4%). The new fuctions of land are: shops, houses, stalls, shop house, restaurant, furniture business, workshop, stone cloth business and tourist destinations.